Pilomatrixoma. A case with unusual clinical features. - Boccardi, D.; Menni, S.; Palvarini, M. (European Journal of Pediatric Dermatology, 2001)
A 10-year-old girl with a nodular lesion on the neck is reported. The nodule had arisen about two months before. Due to its rapid increase and its unusual clinical features, the nodule was surgically removed. The pathological findings led to diagnose pilomatrixoma, ruling out malignant tumors. Ultrasonography was performed before removal. However, it was not useful from a diagnostic point of view. The advantages of this non invasive procedure are considered in childhood pre-operating management.